Pengaruh Corporate Social Responsibility (CSR) dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Pertambangan yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Rachmadi, Heksawan; Jumryati, Jumryati (Neraca : Jurnal Akuntansi Terapan, 2024)
This research aims to determine the magnitude of the influence of Corporate Social Responsibility (CSR) and Profitability on the Firm Value of Mining Companies listed on the Indonesia Stock Exchange from 2019 to 2021. This study employs a quantitative approach. The sample for this research was taken using the Purposive Sampling Method, resulting in 30 samples from 10 Mining Companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The data were then analyzed using partial and simultaneous Determination Coefficients. The results of the regression test show that the CSR variable does not have a significant influence on the firm value, while the Profitability variable has a significant influence on the firm value. Thus, the analysis results indicate that (1) The magnitude of the influence of Corporate Social Responsibility (CSR) on the Firm Value is 50.6%, with the remaining 49.4% explained by other variables not included in this study. (2) The magnitude of the influence of Profitability, proxied by Return on Equity, on the Firm Value is 64.4%, with the remaining 35.6% explained by other variables not included in this study. (3) The magnitude of the influence of Corporate Social Responsibility (CSR) and Profitability on the Firm Value is 67.0%, with the remaining 33% explained by other variables beyond the scope of this study.